2017
DOI: 10.1186/s13071-017-2239-9
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Role of inhibitors of serine peptidases in protecting Leishmania donovani against the hydrolytic peptidases of sand fly midgut

Abstract: BackgroundIn vector-borne diseases such as leishmaniasis, the sand fly midgut is considered to be an important site for vector-parasite interaction. Digestive enzymes including serine peptidases such as trypsin and chymotrypsin, which are secreted in the midgut are one of the obstacles for Leishmania in establishing a successful infection. The presence of some natural inhibitors of serine peptidases (ISPs) has recently been reported in Leishmania. In the present study, we deciphered the role of these ISPs in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 51 publications
0
17
0
1
Order By: Relevance
“…Similarly, all but one publications on Leishmania ecotin orthologs indicated that the main function of these proteins is protection against intestinal proteases in the gut of the insect Ecotin protects bacteria against human serum-mediated lysis vector, or against contact pathway-mediated bactericidal effects of the host [47,48], or downregulation of inflammatory monocytes and monocyte-derived cells [49]. We found only a single, very recent paper reporting that Leishmania donovani ecotin ortholog LnISP2 is not only a neutrophil elastase inhibitor, but also a MASP-2 inhibitor [40].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, all but one publications on Leishmania ecotin orthologs indicated that the main function of these proteins is protection against intestinal proteases in the gut of the insect Ecotin protects bacteria against human serum-mediated lysis vector, or against contact pathway-mediated bactericidal effects of the host [47,48], or downregulation of inflammatory monocytes and monocyte-derived cells [49]. We found only a single, very recent paper reporting that Leishmania donovani ecotin ortholog LnISP2 is not only a neutrophil elastase inhibitor, but also a MASP-2 inhibitor [40].…”
Section: Discussionmentioning
confidence: 99%
“…L. donovani promastigotes (AG83:MHOM/IN/1983/AG83) were used in our experiments. ISP2KD and ISP2 overexpressed (ISP2OE) Leishmania parasites were prepared in our lab as described previously ( 24 ). All the cell lines promastigotes were maintained according to Mandal et al ( 25 ) at 25°C in 25 cm 2 flasks in fresh Medium-199 supplemented with 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…All the cell lines promastigotes were maintained according to Mandal et al ( 25 ) at 25°C in 25 cm 2 flasks in fresh Medium-199 supplemented with 10% FBS. The ISP2KD and ISP2OE cells were maintained in M199 media supplemented with neomycin (G418) at 200 µg/ml concentration ( 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…Those observations helped to define ISP2 as a virulence factor required for successful infection by L. major (21, 22), but the potential contribution of ISP2 in modulating NE activity and infection in VL has not been investigated. mRNA to ISP2 was detected in L. donovani (23), and studies in vitro using recombinant ISP2 from this species [ L. donovani inhibitor of serine peptidase 2 (LdISP2)] showed that it can inhibit trypsin and NE (24, 25). Recombinant ISP2 also inhibited serine peptidases of the sand fly midgut in vitro , and transgenic lines knocked down to ISP2 were more susceptible to sand fly peptidases and less fit to survive in the midgut (23).…”
mentioning
confidence: 99%
“…mRNA to ISP2 was detected in L. donovani (23), and studies in vitro using recombinant ISP2 from this species [ L. donovani inhibitor of serine peptidase 2 (LdISP2)] showed that it can inhibit trypsin and NE (24, 25). Recombinant ISP2 also inhibited serine peptidases of the sand fly midgut in vitro , and transgenic lines knocked down to ISP2 were more susceptible to sand fly peptidases and less fit to survive in the midgut (23). Other studies applying treatment of infected RAW cells with recombinant LdISP2 showed slight reduction of infection and of NO production (25).…”
mentioning
confidence: 99%